Relationship between potentiometric surface and abnormally low pressure in the Yanchang Formation, Zhenjing area, Ordos Basin, China - Chao Li; Huixi Lin; Yukai Qi; Likuan Zhang; Lan Yu; Yuhong Lei; Guiqiang Qiu; Liyuan Ma; Hanwen Hu (Natural Gas Industry B)
Abnormally low pressure commonly develops in petroliferous basins. It is closely associated with hydrocarbon distribution and can hinder safe drilling operations. Potentiometric surface is one of the causes of abnormally low pressure, but the relationship between such surface and abnormal pressure has not attracted much research attention. In this paper, a method is proposed for quantifying the potentiometric surface of the tight oil reservoir of the Upper Triassic Yanchang Formation in the Zhenjing area, southern Ordos Basin, China. This method involves screening pressure data that reflect real pore pressure conditions underground and analyzing the formation sealing conditions in the reservoir based on fracture development and the chemical characteristics of the formation water. The relationship between the potentiometric surface and the abnormally low pressure observed in the study area is discussed. The results show that the pressure coefficient of the Yanchang Formation in the Zhenjing area is 0.85–1.02, with an average of 0.93, indicating a state between abnormally low pressure and normal pressure. The Yanchang Formation has complex sealing conditions, with favorable overall sealing and a locally open hydrodynamic environment controlled by sand body connectivity and fault activity. We proposed a method to calculate the potentiometric surface using the measured pressure data with a pressure coefficient close to 1. The potentiometric surface is 1040–1200 m, with a high value in the northwest and a low value in the southeast, and it is 0–350 m below the ground level. The pressure coefficient was calibrated with an average of 1, with the potentiometric surface used as the starting point, indicating that the low pressure coefficient may be caused by the potentiometric surface below the ground level. The results have theoretical implications for the analysis of formation pressure characteristics in areas or basins with comparable geological conditions, and practical implications for the analysis and development of oil and gas.